Emprego de compostos organometálicos mononucleares de paládio(II) na ativação de macrófagos peritoneais de camundongos - de Almeida, Eduardo Tonon [UNESP]; Mauro, Antonio Eduardo [UNESP]; Santana, Anderson Martinez [UNESP]; Godoy Netto, Adelino Vieira de [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Sociedade Brasileira de Química, 2005)
The immune responses are mediated by a variety of cells that, when activated, produce a number of molecules. Macrophages are the first cells to take part in the immune response releasing many compounds in the extracellular environment such as H2O2. Taking into account this aspect we evaluated the activation of an immunological system, in vitro, by determining the H2O2 released in cultures of peritoneal macrophage cells from Swiss mice in the presence of organopalladated compounds of the type [Pd(dmba)(X)(dppp)], dmba = N,N-dimethylbenzylamine, dppp = 1,3-bis(diphenylphosphine)propane, X = Cl, N3, NCO, NCS. An excellent activation of macrophages by the [Pd(dmba)(X)(dppp)] compounds was observed and the influence of the X ligand on the immune response could be verified.
Activation of mice peritoneal macrophages by palladium(II) organometallic mononuclear compounds
Keywords: palladium(II) complexes; macrophages; hydrogen peroxide